1982
DOI: 10.3171/jns.1982.57.6.0791
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic encephalitis produced by selective non-occlusive intracarotid BCNU injection in dogs

Abstract: A selective non-occlusive technique was developed for administration of BCNU (1,3-bis(2-chloroethyl)-1-nitrosourea) into the internal carotid artery of the dog, and the neuropathological effects in the brain were studied. One out of three dogs showed ipsilateral hemorrhagic necrotizing encephalitis at doses of 102 mg/sq m, and all of three dogs showed similar but more severe pathology at doses of 215 to 232 mg/sq m. This study and previous studies in the dog and monkey suggest definite thresholds above which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
19
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…4 Hemorrhagic necrosis, most prominent in white matter, and neutrophils and mononuclear cells within damaged vessel walls and in the perivascular space were present in the ipsilateral cerebrum of dogs examined 3 to 7 days after experimental intracarotid injection of a lipidsoluble nitrosourea chemotherapeutic agent. 7 Clinical signs in this case were indicative of right cerebral injury, and pathologic findings were confined to the right meninges, cerebrum, hippocampus, and thalamus. Ketamine, the primary component of the injected mixture, is hyperosmolar with an acidic pH, but a study of myotoxicity of ketamine after intramuscular injection concluded that ketamine also had a direct cytotoxic effect.…”
mentioning
confidence: 97%
See 4 more Smart Citations
“…4 Hemorrhagic necrosis, most prominent in white matter, and neutrophils and mononuclear cells within damaged vessel walls and in the perivascular space were present in the ipsilateral cerebrum of dogs examined 3 to 7 days after experimental intracarotid injection of a lipidsoluble nitrosourea chemotherapeutic agent. 7 Clinical signs in this case were indicative of right cerebral injury, and pathologic findings were confined to the right meninges, cerebrum, hippocampus, and thalamus. Ketamine, the primary component of the injected mixture, is hyperosmolar with an acidic pH, but a study of myotoxicity of ketamine after intramuscular injection concluded that ketamine also had a direct cytotoxic effect.…”
mentioning
confidence: 97%
“…Time of death following intraarterial injection in prior reports was 5 min, 1,9 6 hr, 2 up to 24 hr, 4 and 3-7 days. 7 No convincing evidence of neuronal necrosis or perivascular edema was detected in the brain of cattle that died 5 min after inadvertent injection of a lipidbased antibiotic into the right auricular artery. 1 Neuronal necrosis was reported in a cow that died within 5 min of intracarotid injection of chloramphenicol, 9 although the very short time from injection to death suggests that neuronal changes might have been artifactual.…”
mentioning
confidence: 99%
See 3 more Smart Citations